2016
DOI: 10.1166/jbn.2016.2254
|View full text |Cite
|
Sign up to set email alerts
|

Single-Layer Graphene Enhances the Osteogenic Differentiation of Human Mesenchymal Stem Cells In Vitro and In Vivo

Abstract: In recent years, although several studies have demonstrated the potential of graphene-coated substrates in promoting attachment, proliferation and differentiation of osteoblasts and mesenchymal stem cells (MSCs), the effects of single-layer graphene on the osteogenic differentiation of human MSCs (hMSCs) remains unclear, especially in vivo. In this study, we transferred chemical vapor deposition (CVD) grown single-layer graphene to glass slides and observed its effects on adhesion, proliferation and osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…It has been shown that graphene may enhance osteogenic differentiation of SCs [72,73]. Moreover, our recent data also suggest the beneficial impact of graphene oxide (GO) on proliferative capacity, viability and differentiation potential of umbilical cord tissue-derived MSCs, which confirms the possibility of future graphene employment in tissue repair [76].…”
Section: Synthetic Biomaterialssupporting
confidence: 62%
“…It has been shown that graphene may enhance osteogenic differentiation of SCs [72,73]. Moreover, our recent data also suggest the beneficial impact of graphene oxide (GO) on proliferative capacity, viability and differentiation potential of umbilical cord tissue-derived MSCs, which confirms the possibility of future graphene employment in tissue repair [76].…”
Section: Synthetic Biomaterialssupporting
confidence: 62%
“…Graphene coatings can provide an opportunity to overcome these limitations. Titanium and some of its industrially relevant alloys were shown to exhibit greatly improve cell adhesion and osteogenic differentiation of HMSCs and MC3T3‐E1 cells both in vitro and in vivo, when coated with graphene, rGO, and even GO ( Figure ) using polydopamine or PEI as adhesive layers …”
Section: Interactions Between Graphene Derivatives and Tissuesmentioning
confidence: 99%
“…The most dominant cell types used in the included articles were mesenchymal stem cells (MSCs), including human adipose-derived stem cells (hADSCs), [17][18][19][20][21][22] Goat ADSCs, 23 human dental pulp stem cells (hDPSCs), 24 human alveolar bone marrow stem cells (hABMSCs), 25 human periodontal ligament stem cells (hPDLSCs), 26,27 and bone MSCs (BMSCs), [28][29][30][31] such as human BMSCs 19, 32-41 (hBMSCs), murine BMSCs (mBMSCs), 4, 42-49 rabbit BMSCs (rBMSCs), 50 murine MSCs cell line C3H10T1/2 51,52 and Caprine BMSCs (cMBSCs). 53 The type of the MSCs in fifteen studies 19,32,36,40,[54][55][56][57][58][59][60][61][62][63][64] was not defined. Sixteen studies used preosteoblast cells, 14,[65][66][67][68][69][70][71][72][73][74]…”
Section: Cell Sourcesmentioning
confidence: 99%
“…Different types of graphene used in the included studies were pristine graphene, 19 36 GFs, 33 GNSs, 34 GQDs, 94 and nanosized graphene 18 (NGO).…”
Section: Graphene Typesmentioning
confidence: 99%
See 1 more Smart Citation